2006
DOI: 10.1074/jbc.m605482200
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Proteolytic Processing of the Capsular Caf1 Antigen of Yersinia pestis for Major Histocompatibility Complex Class II-restricted Presentation to T Lymphocytes

Abstract: We studied the mechanisms of antigen presentation of CD4 T cell epitopes of the capsular Caf1 antigen of Yersinia pestis using murine bone marrow macrophages as antigen presenting cells and T cell hybridomas specific for major histocompatibility complex (MHC) class II-restricted epitopes distributed throughout the Caf1 sequence. The data revealed diversity in the pathways used and the degrees of antigen processing required depending on the structural context of epitopes within the Caf1 molecule. Two epitopes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 43 publications
2
37
0
2
Order By: Relevance
“…We mapped the major immunodominant major histocompatibility complex (MHC) class IIrestricted epitopes of rCaf1 in two inbred strains of mice (23 We used antigen presentation to T-cell hybridomas in vitro as a sensitive technique to study the role of cpCaf1 structure in antigenicity (23,24). We measured the responses of Caf1-specific T-cell hybridomas to cpCaf1 and rCaf1 presented by bone marrow macrophages.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We mapped the major immunodominant major histocompatibility complex (MHC) class IIrestricted epitopes of rCaf1 in two inbred strains of mice (23 We used antigen presentation to T-cell hybridomas in vitro as a sensitive technique to study the role of cpCaf1 structure in antigenicity (23,24). We measured the responses of Caf1-specific T-cell hybridomas to cpCaf1 and rCaf1 presented by bone marrow macrophages.…”
Section: Resultsmentioning
confidence: 99%
“…Macrophages were grown from femoral bone marrow cells of BALB/c (H-2 d ) and BALB.B (H-2 b ) mice in the presence of macrophage colony-stimulating factor as described previously (12) and activated by treatment overnight with 1 ng of gamma interferon (R&D Systems, Abingdon, United Kingdom)/ml before use as antigen-presenting cells in T-cell assays. The T-cell hybridomas specific for four epitopes of Caf1 (7- (23).…”
Section: Methodsmentioning
confidence: 99%
“…We also show that aggrecan-specific B cells are more efficient at presenting aggrecan than macrophages and, as previously reported for tetanus toxoid, 22 equally as efficient APC as DC. We, 26,59 and others (reviewed in ref. 60), have previously shown that the intracellular origin of the MHC class II molecules used to form peptide-MHC complexes can profoundly influence subsequent CD4 + T cell activation.…”
Section: Discussionmentioning
confidence: 99%
“…Позднее при изучении механизмов презен-тации CD4 T-клеточных эпитопов F1 на мо-дели макрофагов из костного мозга мышей и T-клеточных гибридом было выявлены четыре эпитопа, взаимодействующих с эукариотичес-кими белками главного комплекса гистосов-местимости (MHC) класса II и использующих различные пути презентации [73]. Два из них расположены на C-конце глобулярного доме-на (134-147 и 123-136) и презентируются вновь синтезированными антигенами MHC класса II после лизосомального процессинга при низких значениях pH.…”
Section: иммуногенная активность капсульного антигенаunclassified
“…Кроме того, формирование более выраженного по силе и протективности тимусзависимого иммунного ответа происходит, вероятно, в организме тепло-кровного животного или человека в случае попа-дания в него F1, агрегированной с тимусзависи-мыми детерминантами других белков чумного микроба или при введении очищенного препа-рата F1 в организм, ранее контактировавший с возбудителем чумы. В то же время T-клеточные эпитопы, индуцирующие клеточное звено им-мунного ответа, присутствуют и в собственной структуре субъединицы капсульного антигена [73,96]. Следует отметить, что основное значение в формировании иммунитета к чуме принадле-жит именно клеточным иммунным процессам и главным образом T-системе лимфоцитов [24].…”
Section: иммуногенная активность капсульного антигенаunclassified